Estimation of Stature from Percutaneous Tibia Length of Indigenes of Bekwara Ethnic Group of Cross River State, Nigeria - Ugochukwu Godfrey Esomonu; Lukpata Philip Ugbem; Ben-Abua M Donald (Wolters Kluwer Medknow Publications, 2016)
Estimating stature by developing linear regression equations which incorporate the features of fragmented body parts or human skeletal remains has been employed by many forensic anthropologists to establish the identity of victims of mass disaster although all formulas are ethnic, age, and gender specific. The study is aimed at using the percutaneous tibia length (PCTL) to deriving a specific regression equation formula which could be used to estimate the stature of adult indigenes of Bekwara ethnic group in Cross River State. A total number of 600 subjects within the age range of 21-45 years were recruited randomly for this research (300 males and 300 females). Observed height and PCTL were measured using the standard anthropometric technique, respectively. Stature was estimated from PCTL using simple regression analysis. On analysis of the data, the mean PCTL for male was found to be 43.60 ± 2.31 cm while that of female was 42.55 ± 2.83 cm. The observed height was 165.80 ± 6.88 cm and 156.70 ± 6.06 cm for male and female, respectively. Statistical analysis showed that the male values of the measured parameters were significantly higher than the corresponding female values. The linear regression equations derived for male and female for the estimation of height using the PCTL was found to be 5.289 (PCTL) + (−64.78) and 4.230 (TL) + (−23.28), respectively. It was concluded that stature can be estimated using the length of an intact mutilated leg. Thus, the data of this study are recommended in anthropological studies for stature estimation among the ethnic group under study.